Sulfonamide-containing copper(II) metallonucleases: Correlations with in vitro antimycobacterial and antiproliferative activities - Nakahata, Douglas H.; de Paiva, Raphael E.F.; Lustri, Wilton R.; Ribeiro, Camila M. [UNESP]; Pavan, Fernando R. [UNESP]; da Silva, Gisele G.; Ruiz, Ana L.T.G.; de Carvalho, João E.; Corbi, Pedro P. (Elsevier, 2018)
The bis-(1,10-phenanthroline)copper(I) complex, [Cu(I)(phen)2]+, was the first copper-based artificial nuclease reported in the literature. The biological and ligand-like properties of sulfonamides make them good candidates for fine-tuning the reactivity of the [Cu(phen)2] motif with biomolecules. In this context, we developed three novel copper(II) complexes containing the sulfonamides sulfameter (smtrH) and sulfadimethoxine (sdmxH) and (N^N)-bidentate ligands (2,2′-biyridine or 1,10-phenantroline). The compounds were characterized by chemical and spectroscopic techniques and single-crystal X-ray crystallography. When targeting plasmid DNA, the phen-containing compounds [Cu(smtr−)2(phen)] (1) and [Cu(sdmx−)2(phen)] (2) demonstrated nuclease activity even in the absence of reducing agents. Addition of ascorbic acid resulted in a complete cleavage of DNA by 1 and 2 at concentrations higher than 10 μM. Experiments designed to evaluate the copper intermediates involved in the nuclease effect after reaction with ascorbic acid identified at least the [Cu(I)(N^N)2]+, [Cu(I)(sulfa)(N^N)]+ and [Cu(I)(sulfa)2]+ species. The compounds interact with DNA via groove binding and intercalation as verified by fluorescence spectroscopy, circular dichroism (CD) and molecular docking. The magnitude and preferred mode of binding are dependent on the nature of both N^N ligand and the sulfonamide. The potent nuclease activity of compounds 1 and 2 are well correlated with their antiproliferative and anti-M. tuberculosis profiles. The results presented here demonstrated the potential for further development of copper(II)-sulfonamide-(N^N) complexes as multipurpose metallodrugs.
Keywords: Anti-M. tuberculosis activity; Antiproliferative activity; Copper(II); Metallonucleases; Sulfonamides